Northern Exposures - Clark, Jordan (University of Wisconsin--Stout. Research Services, 2015)
This body of work draws from real spaces, nature, and the process of applying paint. This leads to me to consider spaces outside and inside, natural phenomena, time, and movement.
Artist statement and photographs of oil paintings.
Keywords: art and design; studio art; Nature in art; College students' art--Wisconsin--Menomonie; oil paintings